A high-resolution radiation hybrid map of the river buffalo major histocompatibility complex and comparison with BoLA - Stafuzza, N. B. [UNESP]; Greco, A. J.; Grant, J. R.; Abbey, C. A.; Gill, C. A.; Raudsepp, T.; Skow, L. C.; Womack, J. E.; Riggs, P. K.; Amaral, M. E J [UNESP] (Wiley, 2013)
The major histocompatibility complex (MHC) in mammals codes for antigen-presenting proteins. For this reason, the MHC is of great importance for immune function and animal health. Previous studies revealed this gene-dense and polymorphic region in river buffalo to be on the short arm of chromosome 2, which is homologous to cattle chromosome 23. Using cattle-derived STS markers and a river buffalo radiation hybrid (RH) panel (BBURH5000), we generated a high-resolution RH map of the river buffalo MHC region. The buffalo MHC RH map (cR5000) was aligned with the cattle MHC RH map (cR 12000) to compare gene order. The buffalo MHC had similar organization to the cattle MHC, with class II genes distributed in two segments, class IIa and class IIb. Class IIa was closely associated with the class I and class III regions, and class IIb was a separate cluster. A total of 53 markers were distributed into two linkage groups based on a two-point LOD score threshold of ≥8. The first linkage group included 32 markers from class IIa, class I and class III. The second linkage group included 21 markers from class IIb. Bacterial artificial chromosome clones for seven loci were mapped by fluorescence in situ hybridization on metaphase chromosomes using single- and double-color hybridizations. The order of cytogenetically mapped markers in the region corroborated the physical order of markers obtained from the RH map and served as anchor points to align and orient the linkage groups. © 2012 The Authors, Animal Genetics © 2012 Stichting International Foundation for Animal Genetics.
Keywords: cattle; comparative map; fluorescence in situ hybridization; major histocompatibility complex; physical map; radiation hybrid map; Animalia; Bacteria (microorganisms); Bos; Bubalus bubalis; Mammalia